ANALISIS BEBAN KERJA SEBAGAI DASAR PENENTUAN INSENTIF PADA PERAWAT RUMAH SAKIT UMUM DAERAH (RSUD) DR. SOEROTO NGAWI - Supadi, Supadi; Purwanto, Wahyu (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
Providing incentives has an effect on work motivation. High workloads should be balanced with high incentives. Dr. Soeroto Hospital as a type C Hospital becomes the first referral center after the primary level has a large variety of cases, especially in the Emergency Room (IGD). The purpose of this study was to find out the workload in the emergency room of Dr. Soeroto Ngawi Hospital and the incentive distribution system. From this study also analyzed the proportion of incentive distribution based on the workload of nurses in the emergency room. This research is a qualitative descriptive study by taking 3 samples, namely 1 nurse as head of the emergency room and 2 nurses taken by random sampling. The three nurses are deeply discussed. There were 18 nurses in the emergency room who were observed using a work sampling for 7 days of observation of work in the morning shift. The main thing in this research is that the workload of the emergency room nurse at RSUD Dr. Soeroto Hospital is classified as heavy with workloads above 80%. It is not yet comparable between the existing incentive systems and the workload borne by the IGD nurses.